A Spinasteryl Glycoside from Ipomoea turpethum L. Herb (Stem) Growing in Bangladesh (Journal of Bangladesh Academy of Sciences, 2012)
Chromatographic purification and spectroscopic analysis of the constituents from the stem  extract of Ipomoea turpethum L. reported 22, 23-dihydro-?-spinasteryl-?-D glucoside (H-1) in  addition to salicylic acid and N-p-comaryltyramine. The structures were elucidated by  spectroscopic analysis including 1H-NMR and 13C-NMR, 1H-1H COSY, 1H-13C COSY, HMQC,  HMBC, UV and IR spectroscopy. 22, 23-dihydro-?-spinasteryl-?-D-glucoside is first reported  from Ipomoea turpethum. DOI: http://dx.doi.org/10.3329/jbas.v36i1.10906 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 1, 13-17, 2012